PENGARUH INTENSITAS PENGGUNAAN APLIKASI TIKTOK TERHADAP KONTROL DIRI PADA SISWA KELAS X SMAN 50 JAKARTA - Cahyani, Rini Gusti (PABKI (Perkumpulan Ahli Bimbingan dan Konseling Islam) Indonesia, 2024)
This study is motivated by the phenomenon that class X students use the TikTok application more which can affect students' ability to control themselves. The study aims to find out whether there is an effect of the intensity of using the TikTok application on the self-control of Class X Students of SMAN 50 Jakarta. The research method used is correlational quantitative method (Correlation Studies). The research was conducted at SMAN 50 Jakarta with a population of 251 students. The research sample amounted to 72 class X students, who were taken using purposive sampling technique with criteria, namely having the TikTok application, active TikTok users, and passive TikTok users. The data collection tool is a research instrument in the form of a questionnaire. The calculation results were obtained using the Guttman Scale. The results showed that the Fcount value of 9.758 exceeded the Ftable of 2.34 with a significance level of 0.003 kecil dari 0.05. So that the criteria set, the hypothesis Ha which states that the Intensity of Use of the TikTok Application has an influence on Self-Control is accepted. So it can be concluded that there is a significant influence between the intensity of using the TikTok application on self-control in class X students.